Natural variation in Brassica FT homeologs influences multiple agronomic traits including flowering time, silique shape, oil profile, stomatal morphology and plant height in B. juncea - Tyagi, Shikha (Plant science : an international journal of experimental plant biology, 2018)
Copyright © 2018 Elsevier B.V. All rights reserved.